ABO AND RH BLOOD GROUPS DISTRIBUTION IN THE POPULATIONS OF LARESTAN AND LAMERD, FARS PROVINCE, IRAN - M. Saadat; P.Amirshahi; D.D. Farhud (Tehran University of Medical Sciences, 1996)
A total of 3204 ABO and Rh blood groups were investigated in Larestan and Lamerd populations, in Fars province, in Iran. The frequency of the A gene ranged from 16.54% to 21.96, the B gene from 15.85 to 27.77% and that of the d gene from 21.49 to 33.01% ; compared with the gene frequencies of 20.97% for the B and 28.50% for the d in the general population. It seemed that the two populations studied in the present investigation were characterized by a higher B and a lower A gene frequencies. Larestan and Lamerd areas had been malarias for several centuries and because the B phenotype has slight advantage at malarious condition, in appeared that, at least in part, the natural selection counts for the high level of the B gene in Larestanis and Lamerdis compared with that in other populations of Fars province.